The EU’s Democratic Dilemma: Assessing the Rise and Ramifications of Technocratic Government - Yiwen Zhang (SAGE Open)
Amid escalating political and economic challenges, several EU nations have witnessed the emergence of technocratic governments, often perceived as complementary to or alternative for representative democracy. This research endeavors to identify the pivotal determinants of the rise of technocratic governments and to evaluate their prospective political implications. Employing multinomial logistic regression analysis on 285 instances, this study establishes that factors such as economic underperformance, pervasive corruption, party polarization, and surging populism significantly enhance the likelihood of technocratic government inception. Subsequent in-depth case analyses further reveal that the public’s aspiration for efficient governance and the intrinsic paradoxes of party democracy contribute to the phenomenon of technocratic populism. This study underscores the potential discord between technocratic government and representative democracy, emphasizing the need for a more profound exploration and deliberation on efficacious governance.